The multilateral response to the global crisis: Rationale, modalities, and feasibility - Eduardo Fernández-Arias; Andrew Powell; Alessandro Rebucci (Inter-American Development Bank, Research Department, 2009)
The paper reviews the case for a strong multilateral response to the global crisis in emerging markets (EMs). It discusses modalities and feasibility of intervention and its associated risks, depending on country circumstances of fiscal space and liquidity needs. The specific role of Multilateral Development Banks (MDBs) in ensuring the development effectiveness of the fiscal response is also discussed. The paper concludes by highlighting the international financial architecture issues raised by the global crisis that cannot be addressed immediately but will need to be dealt with once the current crisis has been tamed.
Keywords: F3; F33; F53; 330; Global Crisis; Latin America and Caribbean; Multilateral Development Banks; Policy Responses; Finanzmarktkrise; Finanzmarkt; Aufstrebende Märkte; Bankenpolitik; Internationale wirtschaftspolitische Koordination; Entwicklungsbank; Welt